The clinical signifi cance of urethral sphincter hyperkinesis in the treatment of benign prosta???? c hyperplasia - I. I. Belousov (Вестник урологии)
Introduction. Today there is many highly effective surgical approaches in the treatment of benign prostatic hyperplasia (BPH). New technologies in the treatment of BPH continue to be implemented. Despite this in some patients the results of surgical treatment for short-term and long-term monitoring is unsatisfactory.Purpose of research. Тo improve the results of treatment of patients with benign prostatic hyperplasiaMaterials and methods. The functional state of the urethral sphincter was studied in 123 patients with symptomatic BPH. According to the treatment method, all patients were separated into groups. Group 1 - patients with established standard indications for surgical treatment. After surgery, patients with persistent obstructive urination received therapy with a central muscle relaxant for three months. Group 2 - patients with uncomplicated BPH, having hypertonic urethral sphincter and receiving drug therapy according to the established urodynamic patterns.Results. Our analysis of the efficacy of surgical treatment of patients with BPH demonstrates a significant correlation between negative outcomes of surgery for BPH with increased tone of the external urethral sphincter. So, in 70.1% of cases, symptomatic obstructive Low Urinary Tract Symptoms (LUTS) in BPH were accompanied by increased tone of the urethral sphincter from standard parameters. We believe that these changes were related to the anatomical characteristics of nodular hyperplasia.Conclusions. Exactly this fact, that these patients had urethral sphincter dysfunction in 14.5% of cases made for poor effect of surgical treatment of BPH. Use of muscle relaxants centrally acting drug therapy in these cases, significantly improves the urodynamics of lower urinary tract, which is accompanied by regression of LUTS.